The Relationship Between Learning Motivation And Learning Resources Toward Academic Achievement Of Students At Mts Al Azhar Tanjung Bumi Bangkalan - Zainal Abidin; Didit Darmawan (Hikamatzu | Journal of Multidisciplinary, 2024)
This study aims to investigate the effect of learning motivation and learning facilities on the learning achievement of MTs Al Azhar Tanjung Bumi Bangkalan students. Learning achievement is considered a key indicator to evaluate the effectiveness of the education system. Learning motivation and learning facilities are identified as key factors that have the potential to influence student learning achievement. This study uses a quantitative approach by collecting data from 100 students of MTs Al Azhar Tanjung Bumi Bangkalan through questionnaires. Regression analysis will be used to assess the extent to which learning motivation and learning facilities contribute to the variability of student learning achievement. The results show that learning motivation and learning facilities have a significant effect on student learning achievement. Understanding the interaction of these two factors is expected to make a positive contribution to improving the quality of education and creating a learning environment that is more conducive to student learning achievement